The Miraculous World of Kaidan in Yoko Tawada`s novel «Suspects on the Night Train» - Стовба, Анна Сергеевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to analysis of specificity of the fictional world of the postmodernist novel by Yoko Tawada, for which miracle and mystery are essential. The protagonist of the novel in the endless travels by night trains step-by-step loses her national and sexual identity, loses the border between dreams and reality. The fictional space of fantastic, mythological world, essential for the Japanese kaidan, underlines loneliness, homelessness and inner emptiness of the main character.